2021
DOI: 10.1002/adfm.202110782
|View full text |Cite
|
Sign up to set email alerts
|

Scalable, Robust, Low‐Cost, and Highly Thermally Conductive Anisotropic Nanocomposite Films for Safe and Efficient Thermal Management

Abstract: Recently, soaring developments in microelectronics raise an urgent demand for thermal management materials to tackle their “overheating” concerns. Polymer nanocomposites are promising candidates but often suffer from their inability of mass production, high‐cost, poor mechanical robustness, and even flammability. Hence, it is desirable to scalably fabricate low‐cost, robust polymeric nanocomposites that are highly thermally conductive and fire‐retardant to ensure safe and efficient thermal management. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 75 publications
0
63
0
Order By: Relevance
“…For example, as shown in Fig. 8 a, Song et al [ 115 ] reported a phenylphosphonic acid @GNPs (PPA@GNPs)/PVA film using modified GNPs and PVA multilayered films fabricated by a LBL assembly approach, and the resultant films exhibited a high in-plane k of 82.4 W (mK) −1 , high flexibility and high tensile strength of 259 MPa. PPA was chosen as a surface modifier for GNPs filler to enhance the hydrophilicity and fire retardance.…”
Section: High-performance Thermally Conductive Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as shown in Fig. 8 a, Song et al [ 115 ] reported a phenylphosphonic acid @GNPs (PPA@GNPs)/PVA film using modified GNPs and PVA multilayered films fabricated by a LBL assembly approach, and the resultant films exhibited a high in-plane k of 82.4 W (mK) −1 , high flexibility and high tensile strength of 259 MPa. PPA was chosen as a surface modifier for GNPs filler to enhance the hydrophilicity and fire retardance.…”
Section: High-performance Thermally Conductive Filmsmentioning
confidence: 99%
“…Owing to the higher k of RGO films than that of graphite films, RGO heat spreaders show higher heat dissipation ability, and it has been reported that commercial RGO films have been used as flexible heat spreaders in the smartphone of “Mate 20” [ 87 ]. Recently, Song et al [ 115 ] used phenylphosphonic acid@GNPs/PVA film as flexible heater spreader to cool smartphone. As shown in Fig.…”
Section: Applicationsmentioning
confidence: 99%
“…However, the relatively weak hydrogen bonds or Van der Waals force among the adjacent layers are insu cient for stable interfacial bridging. [22] To remedy this limitation, a straightforward and universal complexation was deliberately sought to act as robust interfacial bridging for coupling adjacent layers, such as the coordination bonds between carboxyl groups and metal ions. [32][33][34][35] In detail, the plant-originated TEMPO oxidated cellulose nano brils (TOCNF), [36,37] possessing numerous features involving uniformly microscopic size (0.8-2.0 um) ( Supplementary Fig.…”
Section: Structural and Interfacial Bridging Characterizationmentioning
confidence: 99%
“…[20] Many nacre-inspired approaches mainly focus on mimicking the hierarchical structure for mechanical robustness, while few efforts have taken interlocking and discontinuous characteristics of natural nacre into consideration. [21,22] Actually, gaining deep insight into the synergistic toughening effects of interlocking and rationally utilizing the heterogeneous arrangement would provide promising guidance for designing FTEE with the aim of achieving strain-tolerance and mechanical durability, but still lack theoretic demonstration and remain largely unexploited.…”
Section: Introductionmentioning
confidence: 99%
“…Smart and wearable electronic devices with capabilities such as Joule heating, [1][2][3] electromagnetic interference (EMI) shielding [4][5][6] and piezoresistive sensing [7][8][9] have gained great interest for versatile applications of energy conversion, electronic skin and artificial intelligence, etc. [10,11] Indium tin oxide (ITO) has been widely used as conductive elements for wearable electronic devices benefitting from its low resistance and high transparency. However, the brittleness, large density, complex fabrication processes and high cost of ITO greatly limit its application areas.…”
Section: Introductionmentioning
confidence: 99%